Host dispersal shapes the population structure of a tick-borne bacterial pathogen - Norte, A.C. (2020)
f ticks and their associated pathogens. The life cycle of tick-borne pathogens is complex and their evolutionary ecology is shaped by the interactions with vertebrate hosts and tick vectors (Kurtenbach et al., 2006). This study focused on the ecology and genetic diversity of B. burgdorferi s.l. as a model to investigate the drivers of the population structure and to understand the role of host- associated dispersal on the evolution of tick-borne pathogens. This represents a consequential question in the ecology and evolution of any pathogen. Borrelia burgdorferi s.l. is a bacterial complex of over 20 known genospecies, including the etiologic agents of Lyme borreliosis (Casjens et al., 2011; Margos et al., 2015), whose main vectors are ticks of the genus Ixodes (Eisen & Lane, 2002). These bacteria are widespread in Europe, Asia and North America and are also present in North Africa (Margos, Vollmer, Ogden, & Fish, 2011; Zhioua et al., 1999). Different Borrelia genospecies have different patterns of association with vertebrate reservoir hosts (Humair & Gern, 2000; Kurtenbach, Peacey, et al., 1998) because of the immunological host response, mediated by the action of the host's complement system (Kurtenbach et al., 2002). While B. burgdorferi sensu stricto (s.s.) is a generalist genospecies, Borrelia afzelii is mostly associated with mammalian hosts such as rodents, whereas Borrelia valaisiana, Borrelia garinii and Borrelia turdi are mostly associated with birds (Heylen, 2016; Margos et al., 2011). Because tick vectors cannot move large distances independent of hosts, it has been suggested that host specialization determines the spread and dispersal of B. burgdorferi s.l. genospecies (Kurtenbach et al., 2010; Sonenshine & Mather, 1994). Because birds are both important hosts for some Borrelia genospecies and for various species of vector ticks, they act as a driving force shaping B. burgdorferi s.l. distribution and phylogeographical patterns (Margos et al., 2011; Vollmer et al., 2011). Here, we assessed the role of passerine birds as hosts and dispersers of B. burgdorferi s.l. We tested the hypothesis that infection prevalence with Borrelia genospecie